Relationship between the weight of reindeer calves in autumn and their mother's age and weight in the previous spring - Lenvik, Dag; Bø, Esben; Fjellheim, Anders (Rangifer, 1988)
Age and weight in dams aged less than 5 years old together explain 29% of variation in calves' weight in autumn. Each alone explains 22%. In dams aged 5 to 12 years, weight alone explains 22% while age alone explains only 0.4%. Weight followed by age does not significantly improve the fit in these. The implication of this regarding selection strategy is that the aim should be to ensure that the female populationof a herd should include that smallest possible proportion of 1 to 4 year olds. This age structure can be achieved by slaughtering as many calves (0.5 yr) and young females (1.5 yr) as possible. The lifespan of female recruits and the mean age of the female population of the herd are thus increased. This will also result in an increase in the mean weight of the female population, given that animals aged 5 to 10 years are heavier than 2 to 4 years olds.Reinkalvenes høstvekt relatert til mødrenes vårvekt og alder.Abstract in Norwegian / Sammendrag: For mødre yngre enn 5 år forklarer vekten og alderen sammen 29% av variasjonen i kalvenes høstvekt. Alene forklarer hver 22%. Fra 5 til 12 år forklarer vekten alene 19% mens alderen alene bare forklarer 0,4%. Her gir alder etter vekt ikke signifikant tillegg til forklaringen. For utvalgsstrategien har dette som konsekvns at aldersklassene ett til fire år skal utgjøre en minst mulig andel av hunndyrflokken samlet. Denne aldersstrukturen når man ved å konsentrere hovedslakteuttaket til kalve- og ungsimleårgangene (= 1/2 og 1 1/2 år). Omløpstiden forlenges og gjennomsnittsalderen heves derved innen simleflokken. Ved at aldersklassene mellom fem og ti år er tyngre enn aldersklassene to til fire år, leder dette også til en hevning av gjennomsnittsvekten innen simleflokken.Poronvasojen syksypainon riippuvuus emä n kevät-painosta ja iästä.Abstract in Finnish / Yhteenveto: Alle 5-vuotiaiden vaatimien paino ja ikä yhdessä selittävät 29% vasan syksypainon vaihtelusta. Kumpikin selittää erikseen 22%. 5-12 vuoden ikäisilla vaatimilla paino selittää yksistään 19%, mutta ikä vain 0,4%. Iän riippuvuus painosta ei selittänyt tätä merkisevästi. Valinnan kannalta on tärkeää, että lau-massa om pienin mahdollinen määrä 1-4 - vuotiaita naarasporoja tämä ikäjakautuma saavutetaan teuresta-malla syksyllä mahdollisimman paljon vasoja (0,5 - vuotiaita) ja nuoria naaraita 1,5 - vuotiaita). Naaraiden elinikä pitenee ja keski-ikä laumassa kasvaa. Tämä lisää myös naaraiden keskipainoa, sillä 5-10 vuotiaat naaraat ovat painavampia kuin 2-4 - vuoitaat.
Keywords: reindeer husbandry; slaughtering strategy; breeding; breeding methods; selection strategy